COMPORTAMENTO INGESTIVO DIURNO DE BOVINOS DA RAÇA WAGYU EM SISTEMA DE PASTEJO EXTENSIVO - PIAZZON, Cleiton José; REIS, Marcos Gregory Dias dos; ESCOBAR, Loraine Saldanha; FLORES, Hugo Pereira; SANTOS, Yara Ojeda; OLIVEIRA, Dalton Mendes de (ANAIS DO ENIC, 2018)
-